Impact Story - Aga Khan Foundation Portugal: invest in the crucial first years of life, through the Amas Program - Campos Franco, Raquel (Aprender, 2023)
When the Aga Khan Foundation started its activity in Portugal, it carried out a needs diagnosis to understand where it could add more value. The issue of childhood emerged as fundamental in this country as well, as it was in other countries where the Aga Khan Development Network operates. Above all, the pedagogical dimension of childhood education was identified, which lacked investigation and learning from the professionals’ experience. Childhood Education and Development thus became, from an early age, a priority area of ​​activity for the Aga Khan Foundation in Portugal, first through its support to other organizations, and from the late 1990s onwards with its own activities, assuming, thus, today the Foundation, as almost exclusively operative in the entire spectrum of action. The Childhood Education and Development Program values ​​the first years of life and focuses on the quality of the child-family ecosystem in order to strengthen systems and institutions that invest in the development of children, families and professionals. Since 2016, the Aga Khan Foundation has been developing actions focused on promoting the professional development of nannies and other caregivers in the context of education and childcare in daycare and family daycare. Talking about the social impact of the Aga Khan Foundation in the area of ​​Childhood Education and Development necessarily implies starting with the Centro Infantil Olivais Sul, whose management it assumed from the first moment of intervention in this area. The Centre’s impact derives from a holistic and integrated vision based on explicit childhood pedagogy and its application in a community context, which results in a better quality of life for children. Specifically in the area of ​​the Programa das Amas, the impact is generated today, mainly through dissemination. Via guides that are written and disseminated, training that is designed and organized, and awareness that is carried out in a continuous dialogue with other institutions, with the tutelage and seeking to innovate with concrete proposals that allow the qualification of other professionals.